Membangkitkan Kembali Kelompok Tenun “Aura Cempaka” Desa Sibang Kaja, Abiansemal, Badung-Bali - I Gusti Ngurah Eka Partama; Ni Putu Ary Setyaningsih (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The “Aura Cempaka” Weaving Group (KTAC) is one of the SMEs in the endek weaving craft in Sibang Kaja Village, Abiansemal, Badung. Weaving activities are centered on the “Aura Cempaka” Weaving Building with an area of ​​15x15 m2 which is located in Lateng Hamlet, Sibang Kaja Village. This building was built from the 2017 ABPDes Fund and currently the Drawings and Cost Estimates documents are for renovating the roof, walls and floors and will be equipped with a management room and KM/WC. Non-machine looms (ATBM) assisted by the Badung Regional Government in 2018, the loom number 80 has rusted, so it needs to be replaced so that it can function normally again. During the pandemic KTAC activities have stopped and currently it is necessary to improve skills in weaving. Problem solving used in providing solutions to partner problems, namely: Consultation and Training Methods. This PKM activity has succeeded in preparing Plan Drawings and RAB for Renovation of the Weaving Building and providing assistance to KTAC in the form of 4 weaving combs as well as Weaving Skills Improvement Training starting from 03-12 December 2021 for 4 KTAC members. This PKM has succeeded in improving the weaving skills of KTAC members which initially only produced 2 m of endek cloth per day to 2.5 m per day.